Food advertising on YouTube channels aimed at children in Brazil - Juliana de Paula Matos; Polyanna Botrel Tobias; Lavínia Baldim; Paula Martins Horta (Revista de Saúde Pública, 2023)
ABSTRACT OBJECTIVE To analyze food advertising on YouTube channels aimed at children in Brazil and the interaction of the public with this type of advertising. METHODS We analyzed the 10 most popular videos from the 25 YouTube most-watched channels with content aimed at children in the country in 2018. The presence of general advertising, food brands and food services was identified. When there was advertising in the videos, the foods and their respective brands were described, the first being classified according to the NOVA system. In cases of advertising of a specific food brand without its product having been displayed or mentioned, the classification was carried out according to the predominance of that company products. The number of visualizations and interactions (“likes” and “dislikes”) was also collected. RESULTS General advertising was identified in 45.6% of videos, while food and food service advertising was present in 12.9% and 1.6% of videos, respectively. Food advertisements were mostly represented by ultra-processed products (n = 30; 93.8%). In channels led by Kid YouTubers, there was a higher frequency of general advertising, food and food services in the videos. In these channels, the advertisements of food in general and ultra-processed foods were respectively 2.79 and 2.53 times higher than in videos of channels not led by Kid YouTubers. The number of times videos were tagged “liked” was higher in videos with food advertising (1.67 × 105) compared to videos without food advertising (1.02 × 105), p = 0.0272. CONCLUSION YouTube is a potential medium for children’s exposure and interaction with ultra-processed food advertising. The results of this analysis reinforce the importance of enforcing regulations prohibiting children’s advertising on this platform.